2013
DOI: 10.1159/000354309
|View full text |Cite
|
Sign up to set email alerts
|

Transposable Elements in Fish Chromosomes: A Study in the Marine Cobia Species

Abstract: Rachycentron canadum, a unique representative of the Rachycentridae family, has been the subject of considerable biotechnological interest due to its potential use in marine fish farming. This species has undergone extensive research concerning the location of genes and multigene families on its chromosomes. Although most of the genome of some organisms is composed of repeated DNA sequences, aspects of the origin and dispersion of these elements are still largely unknown. The physical mapping of repetitive seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
3
19
1
Order By: Relevance
“…In Astyanax janeiroensis, the colocalization of 18S rDNA sites with As51 satellite DNA was seen to promote the silencing of ribosomal sites. 45 Similarly, an extensive dispersion of hisDNA H3 and hisDNA H2B-H2A sites was detected on the chromosomes of R. canadum 22 colocalized with some TE, such as Rex1 and Rex3, 20 and with the microsatellite (GA) 15 (present study). This distribution pattern also suggests that not all H3 (48 in total) and H2B-H2A sites (24 in total) could be genetically active, in spite of their generally conserved condition.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In Astyanax janeiroensis, the colocalization of 18S rDNA sites with As51 satellite DNA was seen to promote the silencing of ribosomal sites. 45 Similarly, an extensive dispersion of hisDNA H3 and hisDNA H2B-H2A sites was detected on the chromosomes of R. canadum 22 colocalized with some TE, such as Rex1 and Rex3, 20 and with the microsatellite (GA) 15 (present study). This distribution pattern also suggests that not all H3 (48 in total) and H2B-H2A sites (24 in total) could be genetically active, in spite of their generally conserved condition.…”
Section: Discussionsupporting
confidence: 73%
“…44 Similarly, in R. canadum, the distribution of some microsatellites is also coincident with the Tol2 transposon and Rex1 e Rex3 elements. 20 Thus, the colocalization of microsatellites and TE over extensive areas of the genome also suggests the coevolutionary process of these sequences in this species. In Astyanax janeiroensis, the colocalization of 18S rDNA sites with As51 satellite DNA was seen to promote the silencing of ribosomal sites.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Sometimes, large amounts of the repetitive DNAs might promote rDNA silencing [Vicari et al, 2008], although this is not shown in all cases [Costa et al, 2013]. In our case, the enrichment of 2 out of 3 ribosomal gene clusters with repetitive DNAs probably did not affect their activity, as there are 2 active NOR sites in sterlet according to silver staining data.…”
Section: Heterogeneous Distribution Of Repetitive Dnas In Nor-bearingcontrasting
confidence: 46%